2014
DOI: 10.1155/2014/902343
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute ToxicityIn Vivoof Thermal-Sprayed Silver Containing Hydroxyapatite Coating in Rat Tibia

Abstract: To reduce the incidence of implant-associated infection, we previously developed a novel coating technology using hydroxyapatite (HA) containing silver (Ag). This study examined in vivo acute and subacute toxicity associated with the Ag-HA coating in rat tibiae. Ten-week-old rats received implantation of HA-, 2% Ag-HA-, or 50% Ag-HA-coated titanium rods. Concentrations of silver in serum, brain, liver, kidneys, and spleen were measured in the acute phase (2–4 days after treatment) and subacute phase (4–12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…The entire amount of silver is unlikely to exert systemic toxicity, because silver in the coating material is slowly released and rapidly eliminated from the body. Tsukamoto et al have reported that Ag–HA coating shows neither acute nor subacute toxicity in rats. Therefore, 3% Ag–HA may be regarded as a safe implant processing material for use in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The entire amount of silver is unlikely to exert systemic toxicity, because silver in the coating material is slowly released and rapidly eliminated from the body. Tsukamoto et al have reported that Ag–HA coating shows neither acute nor subacute toxicity in rats. Therefore, 3% Ag–HA may be regarded as a safe implant processing material for use in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This means that ALD can give truly atomic scale control of the deposition process and can produce ultrathin films with excellent uniformity and conformity, even on complex high aspect ratio 3D structures . The coating we describe in this study is so thin that the total quantity of active material is kept to a minimum (below levels of detection by ICP‐MS in our study), which helps to reduce concern relating to systemic toxicity of nanolayer silver‐coated orthopedic implants …”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies examining the antimicrobial potential of silver for dental/orthopedic applications rely on dissolution of Ag particles from either cements or surface coatings for titanium. These studies generally report a >2 log‐fold increase in microbicidal activity, although silver particles are highly mobile and potentially toxic, with their tissue accumulation characteristics being largely unexplored . Investigation of silver‐nanoparticle films that are bonded to titanium is therefore of great interest as a method for reduction of postsurgical osteolytic infections, while preventing the release of potentially toxic quantities of silver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsukamoto et al previously demonstrated that, in a rat tibia model with Ag-HA-coated implants, serum silver levels were sufficiently low to avoid harmful effects, and no degeneration was observed in the brain, liver, kidneys, or spleen. The amount of silver required for Ag-HA coating of femoral replacements in humans is low enough to avoid argyria [34]. In fact, in a 1-year follow-up study, we found that none of the patients developed any adverse reactions to silver from Ag-HA-coated implants in total hip arthroplasties [35].…”
Section: Discussionmentioning
confidence: 99%